Crystal structure of a Zn complex with terephthalate and 1,6-bis(1,2,4-triazol-1-yl)hexane - Taisiya S. Sukhikh; Evgeny Yu. Semitut; Andrei S. Potapov (Acta Crystallographica Section E: Crystallographic Communications, 2018)
A new zinc coordination polymer with rigid benzene-1,4-dicarboxylate (bdc) and flexible 1,6-bis(1,2,4-triazol-1-yl)hexane (btrh), namely poly[[(μ2-benzene-1,4-dicarboxylato)[μ2-1,6-bis(1,2,4-triazol-1-yl)hexane]zinc] dimethylformamide monosolvate], [Zn(C8H4O4)(C10H16N6)]·C3H7NO, was synthesized. According to the single-crystal XRD analysis, the product crystallizes in the P-1 space group and has a layered structure. Analysis of the layered structure reveals {Zn(bdc)} chains which are connected by pairs of btrh ligands. The layers are packed tightly perpendicular to the [1-22] direction, separated by one non-disordered dimethylformamide solvent molecule per formula unit. According to thermogravimetric analysis, the product completely loses this solvent at 453 K; the desolvated compound is stable up to 503 K. As a result of the lack of hydrogen-donor groups, hydrogen bonds are not observed in the structure of the complex; however, an intermolecular C—H...π contact of 3.07 Å occurs.